Thermal characterization of 3D-Printed lattices based on triply periodic minimal surfaces embedded with organic phase change material - Qureshi, Zahid Ahmed; Al Omari, Salah Addin Burhan; Elnajjar, Emad; Mahmoud, Farooq; Al-Ketan, Oraib; Al-Rub, Rashid Abu (Case studies in thermal engineering, 2021)
Owing to their high latent heat of fusion and thermal stability, organic phase change materials (PCMs) are lucrative candidates for utilization in latent heat thermal energy storage systems (LHTES). However, since their low thermal conductivity inhibits their direct usage in such systems, they are often impregnated into a thermally conductive metallic matrix, which exhibits an effective thermal conductivity superior to that of PCM alone. In this study, metallic lattices based on Triply periodic minimal surfaces (TPMSs) are utilized as thermal conductivity enhancers for organic PCMs. TPMS are a class of periodic cellular materials that have been recently studied in several structural, thermo-mechanical, and other applications showing promising performance. However, their utilization with PCM in LHTES systems is a relatively uncharted area of research. Using selective laser sintering technique; four metallic TPMS structures were fabricated, i.e., diamond, gyroid, I-graph and wrapped package-graph (IWP), and primitive, and were later impregnated with two organic PCMs (i.e., RT62HC and RT64HC). The thermal conductivity of both PCMs and TPMS-PCM composite were measured using Transient Plane Source (TPS) method. It was found that the TPMS structures enhanced the thermal conductivity of the PCMs. Moreover, for a fixed porosity and unit cell size, the effective thermal conductivity was found to be a function of the TPMS architecture. A preliminary numerical analysis to compare the heat performance of PCM-alone and PCM embedded with TPMS (primitive) showed clear superiority of the TPMS-PCM composite over the PCM-alone case. Therefore, the utilization of TPMS structures in LHTES could be promising in a bid to increase the performance of organic PCMs.